Prevalence and causes of musculoskeletal impairment in Fundong District, North-West Cameroon: results of a population-based survey. - Smythe, T; Mactaggart, I; Kuper, H; Oye, J; Sieyen, NC; Lavy, C; Polack, S (Wiley, 2017)
Objectives Epidemiological data on musculoskeletal conditions such as degenerative joint diseases and bone fractures are lacking in low- and middle-income countries. This survey aimed to estimate the prevalence and causes of musculoskeletal impairment in Fundong Health District, North-West Cameroon. Methods Fifty-one clusters of 80 people (all ages) were selected using probability proportionate to size sampling. Households within clusters were selected by compact segment sampling. Six screening questions were asked to identify participants likely to have a musculoskeletal impairment (MSI). Par-ticipants screening positive to any screening question underwent a standardized examination by a physiotherapist to assess presence, cause, diagnosis and severity of impairment. Results In total, 3,567 of 4,080 individuals enumerated for the survey were screened (87%). The all-age prevalence of MSI was 11.6% (95% CI: 10.1-13.3). Prevalence increased with age, from 2.9% in children to 41.2% in adults 50 years and above. The majority of MSI cases (70.4%) were classified as mild, 27.2% as moderate and 2.4% as severe. Acquired non-trauma comprised 67% of the diagnoses. The remainder included trauma (14%), neurological (11%), infection (5%) and congenital (3%). The most common individual diagnosis was degenerative joint disease (43%). Over one third (38%) of in-dividuals with MSI had never received medical care or rehabilitation for their condition. Conclusions This survey contributes to the epidemiological data on MSI in low- and middle-income countries. Nearly half of adults aged over 50 years had an MSI. There is a need to address the treat-ment and rehabilitative service gap for people with MSI in Cameroon.